MEDIATION OF CAR FINANCING OF ISLAMIC LAW PERSPECTIVE IN THE CONSUMER DISPUTE RESOLUTION AGENCY (BPSK) IN MATARAM CITY - irma istihara zain (Hukum Islam, 2020)
Abstract: Consumer Dispute Resolution Agency (BPSK) has a role in protecting the rights of consumers when it appears, by completing the resolution of car financing through arbitration, conciliation and mediation. The objective of this research is to emphasize the mediation in car financing in Mataram, explained the causes of disputes arising in BPSK, explaining mediation in car financing in BPSK’s Mataram in perspective of Islamic law. This research conducted Qualitative research methods with a case approach. Settlement of the mediation in the financing of the car based on positive compensation in BPSK through requesting, meeting and termination of the Bank in the context of Islamic law prioritizing the rules of the car, based on the principles of compensation in BPS.Keywords: Mediation, Financing, Islam.